Meat analogs: Prospects and challenges - Sazili, Awis Qurni; Mohammad Rashedi, Ismail Fitry; Hayat, Muhammad Nizam; Kumar, Pavan (Springer Nature, 2024)
Meat has been an integral part of the human diet since time immemorial and has played an important role in fulfilling the nutritional requirement for growth and development in addition to social and cultural roles. Meat is an excellent source of animal proteins having higher bioavailability and digestibility, essential amino acids, lipids, minerals, vitamins, and bioactive peptides.